The Influence of the SAVI Approach and Learning Styles on Student’s Creative Math Skills - BT Yosi Olda Fionika; Kamid Kamid; Evita Anggereini (MEJ (Mathematics Education Journal), 2018)
Learning technique at school should concentrate on developing studentscreativity. Creative thinking ability will be the determinant of individualsuccess. But in fact, students are familiar with routine and simple learning.The SAVI approach is an approach that combines physical movement withintellectual activity. Learning style is the capital of a student to absorbinformation. The method used in this research is quantitative method, whichis the purpose is to know the influence of SAVI approach and learning styleto students' creative thinking ability in mathematics when compared withdirect learning. The instruments used are tests of creative thinking abilitiesand learning styles of students. The result of data analysis using statistical testthat is (1) there is influence of SAVI approach and learning style to studentcreative thinking ability. (2) there is influence of SAVI approach to SAVIcreative thinking ability. (3) there is influence of student learning style tostudent creative thinking ability. (4) there is an interaction between SAVIapproach and learning style to students' creative thinking ability.